e-services for the farmers - Cseh, András (Acta Agraria Debreceniensis, 2012)
Nowadays the different IT tools and use of the internet have appeared almost in every sectors of the economy, so it may give several benefits and help to the agricultural producers. In this article I give a brief overview about e-government and its’ opportunities, then I give a short description of a few important governmental and specialized administration on-line services which are provided to the farmers. According to many experts using of informatics may cause essential change in the operation of the administration because of the fact that the electronic administration may evolve. Generally speaking, today the egovernment services are already an indispensable device to the reformation of the public administration, the modification of services which suits to people's demands and the creation of the more adaptable, clearer public administration. The electronicdocuments are free from formal errors which is either important for clients or offices. The cases can be arranged even from home in 24 hours of the day. The spread and success of the use of electronic services depend not only on the quality of services, but the IT readiness of the target audience is also very important factor. Unfortunately the affect of e-gap is bigger in case of the farmers.